Os reflexos das medidas provisórias 664 e 665 sobre as pens\~oes, o abono salarial e o seguro-desemprego em suas modalidades defeso e formal - Marcelo Abi-Ramia Caetano; André Gambier Campos; José Valente Chaves; Carlos Henrique Corseuil; Leon Faceira Tomelin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The purpose of this text is to consolidate the analysis of social policies that were modified by a legal reform, fostered by the government through the so-called "Medidas Provisórias" no 664 and 665, edited on 30 December 2014. The social policies analyzed in this text are pensions, wage bonuses and unemployment benefits of different types. The idea is to support the debate that will take place in the National Congress, providing empirical evidences about the social policies modified by the mentioned "Medidas Provisórias".
Keywords: H55; H53; 330; survivor benefit; wage bonuses; unemployment benefits